Females of a cannibalistic spider control mutilation of their genitalia by males. (1st August 2019) - Mouginot, Pierick; Uhl, Gabriele
Abstract: When females can mate multiply, the interests of both sexes over female remating may not coincide, leading to selection for adaptations and counteradaptations in males and females. In several orb-weaving spiders, males damage external structures of the female genitalia during copulation, which hinders the female from remating. We investigated whether females have control over the mutilation of their genitalia in the orb-weaving spider Larinia jeskovi . We found that female sexual cannibalism during copulation reduced the number of insertions a male was able to perform and hence limited the probability of genital mutilation by the male. Genital mutilation did not differ between treatments in which females experienced different availabilities of other males before the mating trial: males absent, males near the female ("vicinity group"), and males in the female's web ("web group"). However, traits of the mating male (size, condition) were significantly correlated with the occurrence of cannibalism during mating in "web" and "vicinity" treatments. These results suggest that females have control over mutilation by an early termination of mating, can respond to the availability of potential mates and can alter the probability of mutilation according to certain male traits. Female sexual cannibalism may represent a counteradaptation to genital mutilation allowing females to mate multiply. Abstract : Males of many species monopolize females—a drastic means being the mutilation of female genitalia in orb-weaving spiders. We show that females of a spider selectively avoid mutilation. Our study suggests that females differentially allow mutilation of their genitalia by cannibalizing males. Female choice is based on the presence of other potential mating partners and on the quality of the present partner.